Using Waterfall Method to Design Information System of SPMI STIMIK Sepuluh Nopember Jayapura - Elvis Pawan; Rosiyati H.H Thamrin; Patmawati Hasan; Sariyati H.Y. Bei; Paulisen Matu (International Journal of Computer and Information System (IJCIS), 2021)
Abstract - Conventional filing of SPMI documents is a problem experienced by STIMIK Sepuluh Nopember Jayapura, archiving in this way can result in documents being lost or scattered, in addition to causing difficulties in finding documents during internal and external audits. This study aims to assist institutions in improving their filing systems, so that SPMI data or documents can be stored properly and easily obtained when needed. In designing the information system SPMI STIMIK Sepuluh Nopember Jayapura, using the waterfall method and data modeling using data flow diagrams, while in system testing using the blackbox method and user acceptance test. This research produces an SPMI information system that can be used to archive all types of documents owned by the internal quality assurance agency Based on table 2, as many as 86% of the answers of respondents who answered were very correct (SB), as many as 12% of respondents who answered correctly (B) and 2% answered doubtful or neutral.